Effects of educational intervention on repetition rate of routine digital chest radiography among radiographers in tertiary hospitals at Makkah, Saudi Arabia - Almalki, Abdullah Ahmed G (2019)
Background: Routine digital chest radiography is the common radiological procedure that is performed in a hospital’s Radiology Department. Critical issues will arise if this procedure needs to be repeated. Repetition rate is the total number of repeated chest radiography by radiographers divided by total number of chest radiography that performed by the same radiographer, multiply by hundred. High repetition rate increases a patient’s exposure to radiation dose. It also increases the workload of radiographers and patient waiting time as well as affects the annual budget of the department. In Saudi Arabia, the repetition of routine digital chest radiography was documented at 14.90%, which is above the acceptable standards. Objective: The aim of this study is to develop, implement, and determine the effects of educational intervention on the repetition rate of routine digital chest radiography among radiographers in tertiary hospitals within the Makkah Region. Methods: A quasi-experimental repeated measure was conducted with a control group in tertiary hospitals within the Makkah Region for eight months starting from June 2017. Four out of five tertiary hospitals were selected. Then, two of the four hospitals were combined into an intervention group and the other two combined into the control group. Stratification and a subsequent simple random sampling technique were utilized to select 56 respondents for each group. Pre-post intervention, and follow-up phases were conducted to determine the knowledge, motivation, and skills, and repetition rate among the respondents. The implementation of the educational intervention was after collecting the baseline data. The educational intervention has three objectives which include enhancement of radiographers’ knowledge regarding production of high quality of chest radiography, motivating the radiographers to avoid chest radiograph repetition, and increase the the level of the skills regarding chest radiograph. Data was analyzed using Chi-Square, one-way MANOVA, and two-way repeated MANOVA and MANCOVA using SPSS 22. Results: Out of 56 respondents in each group, 47 (83.9%) respondents in the control group and 49 (87.5%) respondents in the intervention group were retained and analyzed. There were no statistically significant differences between the groups with respect to respondent characteristics, knwledge, motivation, skills and repetition rate at baseline p > 0.05. There were statistically significant differences of rknowledge, motivation, skills and repetition rate between groups at the baseline, post-intervention and follow-up after the covariate was controlled where Wilks’ λ = 0.301, p < 0.001. There were statistically significant differences in the primary and secondary outcome between the time of groups, where Wilks’ λ = 0.744, p < 0.001. There were also statistically significant differences in time*groups with respect to knowledge, motivation, skills and repetition rate, where Wilks’ λ = 0.317, p < 0.001. In other words, the behavioral intervention module was effective in reducing the repetition rate. Conclusion: The educational intervention conducted in this study was found to be effective in reducing the repetition rate among the sample study. The change in repetition rate was attributed to the enhanced knowledge, motivation, and skills of respondents in the intervention group.